Analysis of the Effectiveness of the MSME Empowerment Program in Madura Regency in Improving Community Welfare - Matiniri Matiniri; Kristyan Dwijosusilo; Ika Devy Pramudiana; M Khairul Anwar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study analyzes the effectiveness of the MSME empowerment program in Madura Regency in improving community welfare. Empowerment programs that include entrepreneurship training, access to capital through People's Business Credit (KUR), and business assistance show positive results in increasing the capacity of business actors. Based on survey data, most of the program participants experienced an improvement in business management and marketing skills. The positive impact was also seen in the increase in average household income by 30% and the opening of new jobs. However, challenges remain, especially related to the equitable distribution of benefits in rural areas, low digital literacy, and program sustainability. This study uses a quantitative approach with a survey method, supported by the Theory of Change theory to analyze the impact of programs on socio-economic changes in the community. The results of the study show that the empowerment of MSMEs makes a real contribution to the welfare of the community, although continuous evaluation is needed to ensure the sustainability and equitable distribution of program benefits throughout the Madura Regency area. By strengthening the synergy between the government, financial institutions, and local communities, it is hoped that the impact of MSME empowerment can be more optimal.